La auditoría interna y su incidencia en el control de las operaciones económico financieras en la empresa comercial L.C. Group S.A.C. Tarapoto - periodo 2013 - Mori Bazán, Alberth Michelson (2015)
Audit activity is permanently conditioned by the changing overall, both economic, technological, cultural trends and environments business, so that the audit itself reflects changes adaptation generated. Corporate Social Responsibility is a concept that has burst strength in accounting and administrative doctrine in general and internal audit in particular, as an unavoidable response to major changes in the organizational and social environments experienced in recent decades. This research work focuses precisely determine what internal auditing way affects the economic operations control financial trading company in L.C. GROUP S.A.C. Period 2013. This work also aims to determine which control activities trading company performs L.C. GROUP S.A.C for improving processes have daily movements in their operations and determine the correct measures for better management of the resources used for procedures that the company can make.